Pre-intervention left ventricular mechanical dispersion is increased in patients in need for pacemaker after TAVI. (4th February 2022) - Kaya, E; Klaeboe, LG; Aaberge, L; Haugaa, KH; Edvardsen, T; Skulstad, H
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Purpose: Transcatheter Aortic Valve Implantation (TAVI) is an effective therapy for patients with severe aortic stenosis. Complete atrioventricular block (AVB) that requires permanent pacemaker treatment is a common complication of TAVI and it is reported in up to one fifth of patients. Prediction of this complication could be important. Global longitudinal strain (GLS) and left ventricular mechanical dispersion (LVMD) by speckle tracking echocardiography (STE) are novel techniques that detect subtle changes in myocardial function and are related to myocardial fibrosis. Thus, we aimed to investigate the association between LVMD and AVB development after TAVI. Methods: We retrospectively screened 168 consecutive patients after TAVI. Patients with abnormal ECG and changed conduction pre- and post-TAVI were excluded. Data from the remaining 61 patients were compared to the group of 16 patients in need for a permanent pacemaker. Baseline echocardiograms recorded before TAVI were used to assess GLS and LVMD by STE (Figure). Results: Of the 77 patients analysed, 60% were female (82 ± 7 years old). The mean GLS values were -16.8 ± 4.2% and -16.9 ± 3.7% in AVB and no AVB groups, respectively (p = 0.9). The mean LVMD was 60 ± 19 ms in AVB group and 50 ± 16 ms in no-AVB group (p = 0.04). (Table) Conclusion: LVMD was increased in patients who developed TAVI-induced complete AVB, while GLS could not differentiate between post-procedural normal and abnormal electrical conduction. This finding may be important to identify myocardial properties associated with complete AVB after TAVI.